Proposed new design for Proton R3 Showroom at Lot 76, Seksyen 89A, Jalan Ampang, Kuala Lumpur / Norlizawati Yaacob - Yaacob, Norlizawati (Faculty of Architecture, Planning and Surveying, 2006)
The automotive industry has played a big role to provide job opportunities to a country and the populace. With the development of the technology in automotive field, foreign power would not underestimate Malaysia for it is a small country compared to others. By the power that we possess we could make Malaysia stand in the eyes of the world. To achieve this goal, R3 was given the mandate by Proton to play a part to realize it. The planned objective’s purpose is to monopolize Malaysian automotive industry and to be the best is Asia. Apart from that, R3 hoped to give a good competition to other car constructor such Mercedes Benz, Toyota, Mitsubishi and et cetera. Proton put in their faith in R3 to reproduce manufactured Proton cars in racing specification. R3 has also modified their produced car internal and externally to achieve the status of a race car and accordingly to the strict law specifications from the Department of Road and Transportation. International car manufacturer also has their own car reproducer such as Toyota Racing Development for Toyota, Mitsubishi Motorsport Corporation for Mitsubishi, Subaru Technica International for Subaru and et cetera. With the advancement of new technology, R3 team could deliver the best of their products and sen/ices par to other car racing brands. Location also plays an important role in designing the interior of the showroom to make it parallel with its price and quality.